Δικαιοσύνη by Philo of Alexandria: the ‘justice’ in Hellenistic Jewish context (Circe de clásicos y modernos, 2018)
The aim of this work is to analyze the conceptual structure used by Philo of Alexandria in the definition of the term δικαιοσύνη (“justice”) in Special Laws 4. 136-143. We will examine what is the justice according to Philo and what are the concepts that are constitutive part in the rational process which its definition implies. In addition, we will inquire what are the Greek and biblical influences that delimit the philonic idea of the justice in the legal ambit. In this manner, we will be able to demonstrate that Philo understands the justice not only as the fundament of the regulations codified in the written rules in the legislation of Moses, but also as the virtue of the knowledge of the of the divine realities contained in the laws of the Pentateuch that have their origin in God.
Keywords: Philo of Alexandria; justice; definition; conceptual structure; Law